(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT:This article studies the expressive means of the language, stylistic devices carry a greater amount of information as they show the attitude of the speaker or author toward speaking about the principles and the effect of choice and usage of different language elements in rendering thought and emotion under different conditions of communication.